1989
DOI: 10.1182/blood.v73.2.435.435
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 synergizes with M-CSF in the formation of macrophage colonies from purified human marrow progenitor cells

Abstract: We examined the in vitro stimulative effects of recombinant human interleukin-6 (IL-6, or interferon-beta 2) on purified human bone marrow progenitor cells. IL-6 alone or in combination with erythropoietin (Epo), IL-3, GM-CSF, or G-CSF did not induce colony formation. However, IL-6 strongly synergized with M-CSF in stimulating macrophage colony formation (colony numbers and size). The magnitude of IL-6 synergism with M-CSF was dose dependent; maximal potentiation of M- colony formation was evident at approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…The results obtained from serum-containing and serum-free culture experiments show that the humoral factor(s) in serum drives CD14 1 monocytes into CD14 1 CD1a 2 macrophages but not into CD14 2 CD1a 1 DCs in the presence of GM-CSF plus IL-4, thus leading to the assumption that the factor(s) in the serum acts on CD14 1 monocytes to modify their differentiation. Because IL-6 was reported to have the potential to promote monocyte±macrophage colony formation by haemopoietic progenitor cells (Bot et al, 1989;Jansen et al, 1992), we considered that IL-6 may be involved in the shift of CD14 1 monocytes to CD14 1 CD1a 2 macrophages in cultures supported by GM-CSF plus IL-4. Accordingly, we first examined whether blocking of the signals induced by IL-6 would affect differentiation of CD14 1 monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from serum-containing and serum-free culture experiments show that the humoral factor(s) in serum drives CD14 1 monocytes into CD14 1 CD1a 2 macrophages but not into CD14 2 CD1a 1 DCs in the presence of GM-CSF plus IL-4, thus leading to the assumption that the factor(s) in the serum acts on CD14 1 monocytes to modify their differentiation. Because IL-6 was reported to have the potential to promote monocyte±macrophage colony formation by haemopoietic progenitor cells (Bot et al, 1989;Jansen et al, 1992), we considered that IL-6 may be involved in the shift of CD14 1 monocytes to CD14 1 CD1a 2 macrophages in cultures supported by GM-CSF plus IL-4. Accordingly, we first examined whether blocking of the signals induced by IL-6 would affect differentiation of CD14 1 monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Role of IL-6-mediated signals in the differentiation of CD14 1 cells The data shown in Fig 1C and D suggest that serum components, including cytokines, may influence the differentiation of CD14 1 monocytes into macrophages. Previous reports demonstrated that IL-6 supports the development of monocytes±macrophages (Bot et al, 1989;Jansen et al, 1992). It is possible that IL-6 in the serum may be responsible for the population of CD14 1 CD1a 2 cells in serum-containing cultures supplemented with GM-CSF plus IL-4.…”
Section: Phenotype Of Cells In Culture Of Cd14 1 Cells In the Presencmentioning
confidence: 98%
“…'~~,~~~ Recently interleukin-6 was demonstrated to interact synergistically with GM-CSF to enhance he-matop~iesis,'~~ however another study failed to support these observations. 143 The myelopoiesis enhancing activity attributed to IL-6 resembles that of G-CSF, with which IL-6 has 25.7% amino acid suggesting a role for IL-6 in the treatment of various granulocytopenias.…”
Section: Interleukin-6mentioning
confidence: 99%
“…The mononuclear phagocyte (MNP) lineage depends critically on the presence of the monocyte-macrophage colony-stimulating factor (CSF-1 or M-CSF) but their differentiation may be modulated by the presence of other growth factors, such as interleukin (IL) -6 and the granulocyte-macrophage colony-stimulating factor (GM-CSF) [1]. For example, IL-6 has been reported to synergize with CSF-1 [2] and GM-CSF [3] in the formation of M colonies from human bone marrow progenitor cells and to promote maturation of monocytes into M [4]. GM-CSF is known to stimulate monocyte and tissue M proliferation [5] and to enhance CSF-1-induced proliferation of M [5].…”
Section: Introductionmentioning
confidence: 99%